Peran Mikrobiologi dalam Bidang Pertanian untuk Menunjang Ketahanan Pangan dan Keberlanjutan Ekosistem : Kajian Literatur - Fidar Kristiana Zai; Natalia Kristiani Lase (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Agricultural microbiology plays an important role in supporting the sustainability of the agricultural sector, contributing to global food security. Microorganisms, such as bacteria, fungi and algae, have various roles in increasing soil fertility, controlling plant pathogens and supporting biodiversity. This research aims to explore the role of microbiology in supporting environmentally friendly and sustainable agriculture. Through observations of various applications of microorganisms in agriculture, it was found that microorganisms can function as biopesticides, biofertilizers and organic waste processors. The research results show that microorganisms are able to optimize agricultural yields, improve soil health, and reduce dependence on synthetic chemicals.